2014
DOI: 10.4028/www.scientific.net/amm.695.783
|View full text |Cite
|
Sign up to set email alerts
|

New Topology of Single-Phase Segmented Rotor Field Excitation Flux Switching Machine for High Density Air-Condition

Abstract: Various topologies of 3 phase and single phase Field Excitation Flux Switching Machines (FSMs) have been develop recently due to the advantages of veriable flux capability of DC Field Excitation coil located on the stator as well as robust single piece rotor structure suitable for high speed applications. However, the fundamantel principles of the develop machine with salient pole rotor, requires overlap winding between armature and FEC, creating the problems of high end coil, huge size of motor as well as hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…The average torque achieved by 12S-14P SFWFM with toroidal DC winding is far better than the designs discussed before but this machine has high torque ripples which should be consider in future for better characteristics [40]. Recent research has shown that single-phase SFWFMs [38] and outer rotor SFWFM [42] have less iron losses, copper losses, less weight, and high efficiency but the average torque of proposed topologies needs improvement. In [43], the author analysed a new structure of SFWFM which has non-overlap armature and field windings and the rotor is robust.…”
Section: Average Torque and Efficiencymentioning
confidence: 80%
See 2 more Smart Citations
“…The average torque achieved by 12S-14P SFWFM with toroidal DC winding is far better than the designs discussed before but this machine has high torque ripples which should be consider in future for better characteristics [40]. Recent research has shown that single-phase SFWFMs [38] and outer rotor SFWFM [42] have less iron losses, copper losses, less weight, and high efficiency but the average torque of proposed topologies needs improvement. In [43], the author analysed a new structure of SFWFM which has non-overlap armature and field windings and the rotor is robust.…”
Section: Average Torque and Efficiencymentioning
confidence: 80%
“…The cogging torque reduction techniques are normally chosen with the conditions of easy implementation, minimum cost, and machine performances. Various techniques have been published to reduce the cogging torque on both radial-type [52À54] and axial-type PM SFM [55], left vacant space in the area of SFWFMs, as all the designed discussed above have cogging torque especially single phase SFWFMs which have high cogging torque, discussed in [38]. Rotors with stepped skew [56,57] should be adopted in future to reduce the cogging torque and torque ripple under various load conditions.…”
Section: Cogging Torquementioning
confidence: 98%
See 1 more Smart Citation
“…2(c) than single-phase FEFS motor with non-overlap windings. Single-phase 12S-6P FEFS motor with segmental rotor has been designed for high density air-conditioner and discussed in [25]. Due to non-overlapping windings, the proposed motor has less copper losses as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In order to reduce the cost, one of the possible solutions is to replace the PM with a field excitation coil (FEC). For this reason, some wound field FSMs are proposed for low-cost applications [8][9][10]. The wound field FSM is a novel brushless machine having windings located in the stator [11], having advantages of a magnet-less machine, simple construction, low cost, and variable flux control capabilities suitable for various applications when compared with other FSMs.…”
Section: Introductionmentioning
confidence: 99%